Functional hydrogels for the repair and regeneration of tissue defects - Li, Xinlin; Xu, Mengfei; Geng, Zhaoli; Liu, Yi (Frontiers in Bioengineering and Biotechnology, 2023)
Tissue defects can be accompanied by functional impairments that affect the health and quality of life of patients. Hydrogels are three-dimensional (3D) hydrophilic polymer networks that can be used as bionic functional tissues to fill or repair damaged tissue as a promising therapeutic strategy in the field of tissue engineering and regenerative medicine. This paper summarises and discusses four outstanding advantages of hydrogels and their applications and advances in the repair and regeneration of tissue defects. First, hydrogels have physicochemical properties similar to the extracellular matrix of natural tissues, providing a good microenvironment for cell proliferation, migration and differentiation. Second, hydrogels have excellent shape adaptation and tissue adhesion properties, allowing them to be applied to a wide range of irregularly shaped tissue defects and to adhere well to the defect for sustained and efficient repair function. Third, the hydrogel is an intelligent delivery system capable of releasing therapeutic agents on demand. Hydrogels are capable of delivering therapeutic reagents and releasing therapeutic substances with temporal and spatial precision depending on the site and state of the defect. Fourth, hydrogels are self-healing and can maintain their integrity when damaged. We then describe the application and research progress of functional hydrogels in the repair and regeneration of defects in bone, cartilage, skin and nerve tissues. Finally, we discuss the challenges faced by hydrogels in the field of tissue regeneration and provide an outlook on their future trends.